An Analysis of Risk Factor for ARI Incidence in Toddlers in the Working Area of the Liwuto Public Health Center Baubau City - Leniarti Ali; Yuli Febriana (Universitas Mandala Waluya, 2022)
ARI is a disease that ranks first out of the top 10 diseases at the Liwuto Health Center, Baubau City. In 2018 the incidence of ARI in toddlers was 97 (26.1%) cases, in 2019 there were 124 (28.9%) cases and in 2020 period January-November ARI cases in toddlers were 77 (22.9%) cases. This study aimed to determine the analysis of risk factors for ARI incidence in toddlers in the working area of ​​the Liwuto Health Center, Baubau City. The type of study was analytical research using a quantitative approach with a Case-Control Study method. The population was all toddlers aged 1-5 years who suffered from ARI in the 2020 for the January-November period, namely 77 cases. The sampling used simple random sampling to get a case sample of 44 people and 44 people control, while the total sample was 88 people. The method of analysis uses Odds Ratio (OR). The results showed that the risk factors for ARI incidence in toddlers with calculated OR values ​​obtained immunization status OR = 2.1 (LL =0.364; UL =12.106), the clean and healthy lifestyle behavior OR = 3.7 (LL =1.551; UL =9.068 , exposure to cigarette smoke OR = 5.2 (LL =2.096 ; UL =13.149). The conclusion of this study is that immunization status, the Clean and Healthy Lifestyle Behavior and exposure to cigarette smoke are risk factors for ARI incidence in toddlers. It is recommended to Public Health Center can take preventive steps that can reduce the occurrence of ARI.